Kewenangan Gubernur Jawa Barat dalam Menghentikan Proyek Pramestha Resort Town berdasarkan Surat Gubernur Nomor 640/6561/DBMPR dihubungkan dengan Asas Kepastian Hukum - Muhammad Khoirun Najib; Asyhar Hidayat (Bandung Conference Series: Law Studies, 2021)
Abstract. On November 30, 2019, the daily head of the Citarum DAS PPK task force, Dansector 22, West Java Provincial Highways and Spatial Planning, West Bandung Regency PUPR Service, Bandung Regency DPMPTSP conducted a survey to the field in the North Bandung area, precisely in Langensari village, Lembang, Kabupaten Bandung. West Bandung. At that location there is an ongoing development, namely Pramestha Resort Town. The team found indications of technical violations in development in the field that were not in accordance with the zoning directives in the KBU Regional Regulation. And through letter number 640/6561/DBMPR dated December 31, 2019 which was signed directly by the Governor, where in the letter, it was stated that there were four indications of violations of the Zoning Directive in Regional Regulation Number 2 of 2016. Based on the background described previously, the main problem is in this study are as follows: (1) What is the authority of the Governor of West Java in the Pramestha Resort project based on the Governor's Letter Number 640/6561/DEMPR with legal certainty? (2) What is the legal solution for the settlement of environmental disputes between Pramestha Resort and the provincial government of West Java? The researcher uses the data analysis method used in this study is a qualitative normative analysis. Normative because this research is based on existing regulations as positive legal norms and is related to this problem. Qualitative because the data are arranged systematically, then analyzed and described in the form of words, and do not use formulas. Articles 40, 43 and 54 of Regional Regulation No. 2 of 2016 for the North Bandung Region, the Governor as the Regional Head as well as the organizer of the Regional Government based on the Regional Autonomy Principle, the project is based on the Pramestha Resort Town development project based on the Legal Assurance Principle. Abstrak. Pada tanggal 30 November 2019, ketua harian satgas PPK DAS Citarum, Dansektor 22, Dinas Bina Marga dan Penataan Ruang Provinsi Jawa Barat, Dinas PUPR Kabupaten Bandung Barat, DPMPTSP Kabupaten Bandung melakukan survei ke lapangan Kawasan Bandung Utara tepatnya di desa Langensari, Lembang, Kabupaten Bandung Barat. Di lokasi tesebut terdapat pembangunan yang sedang berjalan yaitu Pramestha Resort Town. Tim menemukan indikasi pelanggaran teknis dalam pembangunan dilapangan yang tidak sesuai dengan arahan zonasi dalam Perda KBU. Dan melalui surat nomor 640/6561/DBMPR tertanggal 31 Desember 2019 yang ditandatangani langsung Gubernur, dimana dalam surat tersebut, tercantum ada empat indikasi pelanggaran Arahan Zonasi dalam Perda Nomor 2 Tahun 2016. Berdasarkan latar belakang yang telah diuraikan sebelumnya, maka yang menjadi pokok permasalahan dalam penelitian ini adalah sebagai berikut: (1) Bagaimana kewenangan Gubernur Jawa Barat dalam menghentikan proyek Pramestha Resort berdasarkan Surat Gubernur Nomor 640/6561/DEMPR dihubungkan dengan asas kepastian hukum? (2) Bagaimana solusi hukum terhadap upaya penyelesaian sengketa lingkungan hidup antara Pramestha Resort dengan pemerintah provinsi jawa barat? Peneliti menggunakan metode analisis data yang digunakan dalam penelitian ini adalah analisis normatif kualitatif. Normatif karena dalam penelitian ini berdasarkan kepada peraturan – peraturan yang ada sebagai norma hukum positif dan terkait dengan permasalahan ini. Kualitatif karena data disusun secara sistematis, kemudian di analisis dan digambarkan dalam bentuk kata, dan tidak memakai hitungan rumusan. Berdasarkan pasal 40, 43 dan 54 Perda No. 2 Tahun 2016 tentang Kawasan Bandung Utara, Gubernur sebagai Kepala Daerah sekaligus penyelaenggara Pemerintah Daerah yang berlandaskan Asas Otonomi Daerah berwenang menghentikan proyek pembangunan Pramestha Resort Town berdasarkan Asas Kepastian Hukum.